Effect of cerebellar transcranial magnetic stimulation on soleus Ia presynaptic and reciprocal inhibition. Issue 3 (11th February 2015) - Matsugi, Akiyoshi; Mori, Nobuhiko; Uehara, Shintaro; Kamata, Noriyuki; Oku, Kosuke; Okada, Yohei; Kikuchi, Yutaka; Mukai, Kouichi; Nagano, Kiyoshi
Abstract : Previously, we reported that cerebellar transcranial magnetic stimulation (C-TMS) facilitates spinal motoneuronal excitability in resting humans. In this study, we aimed to characterize the descending pathway that is responsible for the C-TMS-associated cerebellar spinal facilitation. We evaluated the effect of C-TMS on ipsilateral soleus Ia presynaptic inhibition (PSI) and reciprocal inhibition (RI) because the vestibulospinal and reticulospinal tracts project from the cerebellum to mediate spinal motoneurons via interneurons associated with PSI. PSI and RI were measured with a soleus H-reflex test following operant conditioning using electrical stimulation of the common peroneal nerve. C-TMS was delivered before test tibial nerve stimulation with conditioning-test interstimulus intervals of 110 ms. C-TMS did not generate motor-evoked potentials, and it did not increase electromyography activity in the ipsilateral soleus muscle, indicating that C-TMS does not directly activate the corticospinal tract and motoneurons. However, C-TMS facilitated the ipsilateral soleus H-reflex and reduced the amount of soleus Ia PSI, but not RI. These findings indicate that C-TMS may facilitate the excitability of the spinal motoneuron pool via the vestibulospinal or reticulospinal tracts associated with PSI. Cerebellar spinal facilitation may be useful for assessing the functional connectivity of the cerebellum and vestibular nuclei or reticular formation.